2016
DOI: 10.1097/md.0000000000005005
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association between early atopic dermatitis and subsequent attention-deficit or autistic disorder

Abstract: Atopic dermatitis (AD) is one of the common allergic diseases in children. The presence of allergic diseases was found to have association with the risk of developing attention-deficit hyperactivity disorder (ADHD) or autistic spectrum disorder (ASD) in children, but it is still inconclusive. This study was to investigate the longitudinal relationship between AD developed during toddlerhood and subsequent development of ADHD or ASD in later childhood. Toddlers born between 1998 and 2008 and diagnosed with AD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 48 publications
5
50
4
Order By: Relevance
“…As a skin disease, its visibility and accompanying stigma might affect social interactions and performance at school. Eczema has been linked to attention‐deficit hyperactivity disorder (ADHD), possibly through its effect on sleep disturbance, suggesting another possible pathway to lower EA . However, eczema demonstrates a positive socioeconomic gradient, and risks of developing eczema strongly correlate with higher maternal education.…”
Section: Summary Of Study Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a skin disease, its visibility and accompanying stigma might affect social interactions and performance at school. Eczema has been linked to attention‐deficit hyperactivity disorder (ADHD), possibly through its effect on sleep disturbance, suggesting another possible pathway to lower EA . However, eczema demonstrates a positive socioeconomic gradient, and risks of developing eczema strongly correlate with higher maternal education.…”
Section: Summary Of Study Resultsmentioning
confidence: 99%
“…Eczema has been linked to attention-deficit hyperactivity disorder (ADHD), possibly through its effect on sleep disturbance, suggesting another possible pathway to lower EA. [2][3][4] However, eczema demonstrates a positive socioeconomic gradient, and risks of developing eczema strongly correlate with higher maternal education. ADHD and socioeconomic status could be associated with eczema and atopic eczema.…”
mentioning
confidence: 99%
“…Epidemiologic studies indicate that AD is not only associated with other atopic conditions, but also with a broad spectrum of other chronic conditions . There is robust epidemiologic evidence that children with AD are at increased risk for attention‐deficit/hyperactivity disorder (ADHD) . Although a causal relationship cannot be concluded from the existing studies, the following findings suggest a key role of AD in the development and/or manifestation of ADHD.…”
Section: Introductionmentioning
confidence: 96%
“…Atopic dermatitis (AD) constitutes the most prevalent chronic condition in infancy and causes significant morbidity and burden for patients, their families and healthcare systems . Epidemiologic studies indicate that AD is not only associated with other atopic conditions, but also with a broad spectrum of other chronic conditions . There is robust epidemiologic evidence that children with AD are at increased risk for attention‐deficit/hyperactivity disorder (ADHD) .…”
Section: Introductionmentioning
confidence: 99%
“…Children whose skins are disfigured by AD often experience discrimination or stigmatisation (Chernyshov, ). Previous research has suggested that children living with AD have behavioural problems and experience psychological disturbances, especially psychological stress (Barilla, Felix, & Jorizzo, ), anxiety, depression (Cheng et al, ) and attention deficit hyperactivity disorder (ADHD; Lee et al, ). Generally, children living with AD have a significantly lower quality of life than their healthy peers (Lifschitz, ).…”
Section: Introductionmentioning
confidence: 99%